Take note! to accompany cell and molecular biology : concepts and experiments - Karp, Gerald C. (New York : John Wiley & Sons., 2004)
'A collection of figures, diagrams, and art that illustrate key concepts in your text. Each figure appears on its own page so you can take notes during lectures'.
Buku bacaan asas fakulti
Keywords: Cytology -- Pictorial works; Molecular biology -- Pictorial works